Speckle and Gaussian Noise Reduction In Computed Tomography Image Using Weiner Guided Filter - L.Sasi Kumar, Thayalanayaki (International Journal of Advanced Science and Technology, 2020)
Noise is acquainted with the medical pictures because of different factors in clinical imaging.  Noise expulsion channels can deliver the best outcomes relies on its parameter. Clinical picture De noising can assist the doctors with diagnosing the illnesses. Clinical pictures incorporate MRI scan, CT scan, x-ray scan, ultrasound images. The proposed filter is beneficial and performs will in expelling Gaussian noise and speckle noise and its presentation is poor for salt and pepper noise. Trial results are contrasted and other three separating ideas. The outcome pictures quality is estimated by the PSNR, RMSE and MSE. The WG–Filter works at every pixel in a picture is dislodged by a weighted standard of intensity respects from close to pixels.